Alcohol-Specific Social Comparison as a Moderator of the Norms-Behavior Association for Young Adult Alcohol Use - Litt, Dana M. (Addict Behav, 2018)
Research has indicated that individuals high in social comparison orientation (SCO) are more influenced by the behavior and perceived norms of others. However, despite research indicating that behavior is more closely influenced by and modeled on more socially proximal reference groups, most social comparison research to date has utilized global measures of social comparison. As such, research has not examined whether domain-specific (i.e. alcohol-specific social comparisons) and their relation with norms are more predictive of alcohol-related outcomes than global comparisons. As such, the present study aimed to determine whether the previously found relationships between global SCO, descriptive drinking norms and their interaction are still significant when accounting for alcohol-specific SCO and its interaction with descriptive norms in the prediction of drinking willingness and behavior. Results from 355 young adults age 18–20 indicated that the association of alcohol-specific SCO and its interaction with descriptive norms for drinking predicts alcohol-related outcomes (drinking willingness and alcohol consumption), but not alcohol-related negative consequences) above and beyond global SCO. Thus, alcohol-specific SCO may be of particular importance when determining for whom normative based preventive interventions may be the most efficacious.